Flame-retardant heat-insulating foamed ceramic precursor as well as preparation method and application thereof

Through the flame-retardant and heat-insulated foamed ceramic precursor with a specific group distribution ratio, the problem of poor insulation effect of existing ceramics in high temperature environments is solved, and excellent flame-retardant and heat-insulating properties in chemical batteries and electronic equipment are achieved. Suitable for fire protection needs of a variety of equipment.

CN119219424APending Publication Date: 2024-12-31FOSHAN YUNG SHUN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310774891.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing foamed ceramics cannot be used directly as flame retardant and heat-insulating materials, and their flame retardant and heat-insulating effects are not ideal in high temperature environments, making it difficult to meet the fire-proof needs of chemical batteries and electronic equipment.

Method used

Using components such as silicates, boron-containing compounds, organic acids, phosphorus-containing compounds and foaming agents, the flame-retardant and heat-insulated foam can be formed by cross-linking reactions and expansion at high temperatures through specific group distribution ratios and processes. Ceramic precursors achieve active fire protection and physical heat insulation.

Benefits of technology

The flame-retardant and heat-insulating foamed ceramic precursor forms a pore structure at high temperature, has excellent fire resistance and heat insulation properties, can effectively prevent fire from spreading and improve heat insulation effect, and is suitable for chemical power supplies, electrical equipment and electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219424A_ABST
    Figure CN119219424A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant heat-insulating foamed ceramic precursor as well as a preparation method and application thereof. The flame-retardant heat-insulating foamed ceramic precursor comprises the following components in parts by mass: 20-30 parts of silicate, 10-20 parts of a boron-containing compound, 1-15 parts of organic acid, 1-20 parts of a phosphorus-containing compound, 10-40 parts of a foaming agent and 20-100 parts of water. The flame-retardant and heat-insulating foamed ceramic precursor is in a liquid state, can be coated on a part needing to be protected in a plurality of modes such as roll coating, spray coating, film spraying and the like, and is subjected to a decomposition reaction and a cross-linking reaction under heating, high temperature or open fire according to a specific component proportion, so that a foamed ceramic flame-retardant layer is formed in situ, and an active fireproof effect can be achieved; the material has excellent flame-retardant and heat-insulating effects, and is suitable for various chemical power supplies, electrical equipment and electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fireproof products, and in particular to a flame retardant heat insulating foamed ceramic precursor and a preparation method and application thereof. Background Art

[0002] When a chemical battery is short-circuited due to external impact or other reasons, the temperature rises sharply and a large amount of heat is released in a short period of time, resulting in thermal runaway, which often causes fires and poses a serious threat to the safety of life and property of the people. Electrical equipment or electronic equipment also have the problem of fire induced by short circuits. Therefore, chemical power sources, electrical equipment and electronic equipment often need to use suitable flame-retardant and heat-insulating materials to achieve thermal isolation. Existing common flame-retardant and heat-insulating materials such as non-combustible plastics / rubbers, aerogels, foamed silicone, etc. are often passive heat-insulating and flame-retardant. The heat-insulating effect is not ideal when encountering high temperatures. At the same time, materials such as plastics, rubbers, and silicones are easily burned or burned through, causing thermal short circuits, which poses a greater risk. Moreover, in the context of the increasing capacity of single cells in chemical batteries represented by lithium batteries, it is difficult for existing materials to meet the flame-retardant and heat-insulating requirements.

[0003] Foamed ceramics are widely used in green building materials due to their excellent properties such as light weight, high strength, thermal insulation, waterproof and moisture-proof, and sound insulation. Existing foamed ceramics are usually made of silicate minerals such as kaolin, ceramic tile polishing slag, and industrial tailings. A certain amount of foaming agent is added. After mixing, spray drying, pressing, sintering, cutting and other processes, porous ceramics are prepared. They are mainly used as wall insulation materials. The bubbles of existing foamed ceramics are formed by oxidation reaction in the foamed ceramic matrix at the firing temperature of the ceramic material using high-temperature foaming agent materials such as silicon carbide powder to form CO, CO 2 gas; at the same time, the ceramic matrix forms a silicate molten glass with high viscosity at high temperature, which seals the gas generated by the foaming agent inside the melt, causing the whole material to expand and thus obtain foamed ceramics; this foamed ceramic formed by high-temperature foaming-sintering has good heat resistance and non-flammability, but it is already a rigid ceramic and is mainly used as a building material, such as partitions; it cannot be used as a flame retardant and heat-insulating material for batteries, electronics, and electrical equipment to play a role in fire prevention and fire extinguishing.

[0004] Chinese patent CN106673588B "A magnesium oxysulfate cement lightweight foamed brick and its preparation method" discloses a magnesium oxysulfate cement lightweight foamed brick, including: magnesium oxide, magnesium sulfate solution, filler, a first admixture, a second admixture, a reinforcing agent, a flame retardant, a foaming agent, and an organosilicon hydrophobic agent, wherein the first admixture is an inorganic acid or an inorganic salt, and the second admixture is an organic acid or an organic salt, and has good thermal insulation and flame retardant effects, but it is a solid material and cannot be used as a flame retardant and heat insulating material for batteries, electronics, and electrical equipment to play a role in fire prevention and fire extinguishing, and its flame retardant and heat insulating effects still need to be further improved.

[0005] Therefore, it is of great significance to develop a flame retardant and heat insulating foamed ceramic precursor that can be used in batteries, electronics, and electrical equipment and a preparation method thereof. Summary of the invention

[0006] In view of this, the purpose of the present invention is to solve the problem that foamed ceramics in the prior art cannot be directly used as flame retardant and thermal insulation materials, and their flame retardant and thermal insulation effects still need to be further improved. A flame retardant and thermal insulation foamed ceramic precursor is provided, which has excellent flame retardant and thermal insulation effects and is suitable for a variety of chemical power sources, electrical equipment, and electronic equipment.

[0007] Another object of the present invention is to provide a method for preparing the flame retardant and thermal insulating foamed ceramic precursor.

[0008] Another object of the present invention is to provide application of the flame retardant and thermal insulating foamed ceramic precursor.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A flame retardant heat insulating foamed ceramic precursor comprises the following components in parts by weight: 20-30 parts of silicate, 10-20 parts of boron-containing compounds, 1-15 parts of organic acids, 1-20 parts of phosphorus-containing compounds, 10-40 parts of foaming agents and 20-100 parts of water.

[0011] Furthermore, the silicate is one or more of sodium water glass, potassium water glass, lithium water glass, sodium metasilicate, and potassium metasilicate.

[0012] Furthermore, the boron-containing compound is one or more of sodium borate, potassium borate, magnesium borate, calcium borate, boric acid, and boron oxide.

[0013] Furthermore, the organic acid is one or more of formic acid, acetic acid, propionic acid, oxalic acid, malonic acid, and succinic acid.

[0014] Furthermore, the phosphorus-containing compound is one or more of phosphoric acid, hypophosphorous acid, phosphorous acid, sodium phosphate, sodium metaphosphate, sodium hypophosphite, and sodium phosphite.

[0015] Furthermore, the foaming agent is one or more of magnesium hydroxide, basic magnesium carbonate, aluminum hydroxide, boehmite, calcium carbonate, magnesium carbonate, calcium oxalate, and dolomite.

[0016] A method for preparing the flame retardant and thermally insulating foamed ceramic precursor as described in any one of the above, comprising the following steps:

[0017] S1. Weigh each component according to mass;

[0018] S2. Mixing the silicate with an appropriate amount of water until the silicate is fully dissolved, stirring evenly and configuring it as slurry A; mixing the boron-containing compound with an appropriate amount of water until the boron-containing compound is fully dissolved, stirring evenly and configuring it as slurry B; mixing slurry A and slurry B, stirring evenly and obtaining slurry C;

[0019] S3. Mixing the phosphorus-containing compound with an appropriate amount of water until the phosphorus-containing compound is fully dissolved to prepare slurry D, adding slurry D to slurry C obtained in S2 while stirring, and heating to obtain slurry E;

[0020] S4. The organic acid and the remaining amount of water are mixed uniformly to form a solution F, which is added to the slurry E obtained in S3 while being heated and stirred to obtain a slurry G;

[0021] S5. While maintaining stirring, add the foaming agent powder to the slurry G obtained in S4, and stir evenly to obtain the final product.

[0022] Furthermore, the heating temperature in S3 is 50-100°C.

[0023] Furthermore, the stirring speed in S2 and S3 is 30-600 rpm, and the stirring speed in S4 and S5 is 100-1200 rpm.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] (1) The flame-retardant heat-insulating foamed ceramic precursor of the present invention is prepared by a specific component ratio containing a foaming agent, which can actively prevent fire. When subjected to heating, high temperature or open flame, it decomposes by heat, releases water and carbon dioxide, and absorbs a large amount of heat from the heat source. In addition to the role of physical insulation, it can play a role in actively cooling and extinguishing fire.

[0026] (2) The silicates, boron-containing compounds, phosphorus-containing compounds and organic acids in the flame-retardant and heat-insulating foamed ceramic precursor components of the present invention undergo obvious cross-linking reactions when heated to above 150°C, forming a viscous colloid state, and the volume increases rapidly at the same time; in the process of gradual dehydration of the silicates, boron-containing compounds, phosphorus-containing compounds and organic acids themselves, they also react with the active oxides containing Al-O, Ca-O and Mg-O bonds generated by the decomposition of the foaming agent to form a ceramic mixture with high temperature resistance. The higher the temperature, the more obvious the expansion, and gradually dehydrate to form a ceramic structure containing a large number of pores inside, that is, the foamed ceramic flame-retardant layer is formed in situ. The foamed ceramic flame-retardant layer has high refractoriness, good high-temperature heat-insulating effect, can withstand high temperatures without being burned, and has excellent flame-retardant and heat-insulating properties.

[0027] (3) The flame-retardant and heat-insulating foamed ceramic precursor of the present invention is in liquid form and can be coated on the parts to be protected by various methods such as rolling, spraying, and laminating. The thickness and shape can be flexibly controlled, which is convenient for construction. It can be effectively applied to the fields of chemical power sources, electrical equipment, and electronic equipment.

[0028] (4) The flame retardant and thermal insulation foamed ceramic precursor of the present invention has a low foaming temperature and a large foaming volume. On the one hand, it can effectively isolate the fire source. In a closed space, the increase in the volume of the precursor ceramic will cause it to expand and squeeze the space of the fire source, which can better block the spread of fire. On the other hand, as the foaming volume and thickness of the flame retardant and thermal insulation foamed ceramic precursor increase, the heat transfer distance will be increased, thereby improving the thermal insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0030] Figure 1 It is a schematic diagram of the preparation process of a flame retardant and heat insulating foamed ceramic precursor of the present invention.

[0031] Figure 2 This is a photograph of the sample prepared in Example 2 before calcination.

[0032] Figure 3 This is a photograph of the sample prepared in Example 2 after calcination at 400°C.

[0033] Figure 4 This is a photograph of the sample prepared in Example 6 after calcination at 700°C.

[0034] Figure 5 This is a photograph of the sample of Comparative Example 1 after calcination at 400°C.

[0035] Figure 6This is a photo of the sample of Comparative Example 3 after being burned by direct flame of a butane spray gun.

[0036] Figure 7 This is a photo of the sample of Comparative Example 4 after being burned by direct flame of a butane spray gun. DETAILED DESCRIPTION

[0037] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0038] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0039] Example 1

[0040] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0041] S1. Weigh 15 parts of sodium water glass, 15 parts of borax, 4 parts of phosphoric acid, 2 parts of formic acid, 15 parts of magnesium hydroxide, and 45 parts of water according to mass;

[0042] S2. 15 parts of sodium water glass were mixed with 5 parts of water, stirred at 30 rpm for 1 hour, and mixed to form slurry A; 15 parts of borax were mixed with 30 parts of water, stirred at 60 rpm for 2 hours, and mixed to form slurry B; slurry A and slurry B were stirred and mixed at 60 rpm for 1 hour to obtain slurry C;

[0043] S3. Stir 4 parts of phosphoric acid and 6 parts of water at a speed of 30 rpm for 0.5 h, mix them evenly to prepare slurry D, and then add slurry D to slurry C obtained in S2 at a stirring speed of 300 rpm. After adding, heat to 50°C and continue to stir and heat at this speed for 1 h to obtain slurry E;

[0044] S4. 2 parts of formic acid and the remaining 4 parts of water were stirred at 30 rpm for 0.5 h to mix and prepare solution F, and then added to the slurry E obtained in S3, maintained at a temperature of 50 ° C, and stirred at a speed of 300 rpm for 2 h to obtain slurry G;

[0045] S5. While maintaining a stirring speed of 600 rpm, 15 parts of magnesium hydroxide were added to the slurry G obtained in S4, and the mixture was stirred for 1 hour to obtain the final product.

[0046] Example 2

[0047] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0048] S1. Weigh 20 parts of potassium water glass, 18 parts of sodium metaborate, 12 parts of sodium phosphate, 12 parts of acetic acid, 30 parts of aluminum hydroxide, and 90 parts of water according to mass;

[0049] S2. 20 parts of potassium water glass were mixed with 15 parts of water, stirred at a speed of 30 rpm for 1 hour, and prepared as slurry A; 18 parts of sodium metaborate were mixed with 35 parts of water, stirred at a speed of 250 rpm for 1 hour, and after stirring, they were uniformly prepared as slurry B; slurry A and slurry B were stirred and mixed at a speed of 100 rpm for 1 hour to obtain slurry C;

[0050] S3. 12 parts of sodium phosphate and 30 parts of water were stirred at a speed of 200 rpm for 1 hour to uniformly prepare slurry D, and then slurry D was added to slurry C obtained in S2 at a stirring speed of 400 rpm. After the addition, the temperature was raised to 90° C. and the stirring and heating speed was maintained for 2 hours to obtain slurry E;

[0051] S4. 12 parts of acetic acid and the remaining 10 parts of water were stirred at 30 rpm for 0.5 h to mix and uniformly prepare solution F, and then added to the slurry E obtained in S3, maintained at 90 ° C, and stirred at 400 rpm for 2 h to obtain slurry G;

[0052] S5. While maintaining the stirring speed at 900 rpm, add 30 parts of aluminum hydroxide to the slurry G obtained in S4, and continue stirring for 2 hours to obtain the final product.

[0053] Example 3

[0054] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0055] S1. Weigh 15 parts of sodium metasilicate, 10 parts of potassium tetraborate, 6 parts of phosphorous acid, 4 parts of oxalic acid, 10 parts of basic magnesium carbonate, and 75 parts of water according to mass;

[0056] S2. 15 parts of sodium metasilicate were mixed with 20 parts of water, stirred at 120 rpm for 1 hour to obtain slurry A; 10 parts of potassium tetraborate were mixed with 35 parts of water, stirred at 200 rpm for 1 hour to obtain slurry B; slurry A and slurry B were stirred at 200 rpm for 1 hour to obtain slurry C;

[0057] S3. 6 parts of phosphorous acid and 12 parts of water were stirred at a speed of 60 rpm for 2 hours, and the mixture was uniformly prepared into slurry D, and then slurry D was added to slurry C obtained in S2 at a stirring speed of 600 rpm. After the addition, the temperature was raised to 85°C, and the stirring and heating speed was maintained for 2 hours to obtain slurry E;

[0058] S4. 4 parts of oxalic acid and the remaining 8 parts of water were stirred at 150 rpm for 0.5 h to mix and uniformly prepare a solution F, which was then added to the slurry E obtained in S3, and the temperature was maintained at 85 ° C. The stirring speed was 600 rpm for 2 h to obtain a slurry G;

[0059] S5. While maintaining the stirring speed at 800 rpm, 10 parts of basic magnesium carbonate were added to the slurry G obtained in S4, and the mixture was stirred for 2 hours to obtain the final product.

[0060] Example 4

[0061] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0062] S1. Weigh 18 parts of sodium metasilicate, 10 parts of boric acid, 20 parts of sodium polyphosphate, 12 parts of malonic acid, 25 parts of boehmite, and 90 parts of water according to mass;

[0063] S2. 18 parts of sodium metasilicate were mixed with 18 parts of water, stirred at 250 rpm for 1 hour, and then uniformly stirred to prepare slurry A; 10 parts of borax were mixed with 40 parts of water, stirred at 300 rpm for 1 hour, and then uniformly stirred to prepare slurry B; slurry A and slurry B were mixed and stirred at 300 rpm for 1 hour to obtain slurry C;

[0064] S3. 20 parts of sodium polyphosphate and 20 parts of water were stirred at a speed of 360 rpm for 3 hours, and the mixture was uniformly mixed to prepare slurry D, and then slurry D was added to slurry C obtained in S2 at a stirring speed of 360 rpm. After the addition, the temperature was raised to 60° C. and the stirring and heating speed was maintained for 2 hours to obtain slurry E;

[0065] S4. 12 parts of malonic acid and the remaining 12 parts of water were stirred at 180 rpm for 0.5 h to mix and uniformly prepare a solution F, which was then added to the slurry E obtained in S3, and the temperature was maintained at 60 ° C. The stirring speed was 600 rpm for 2 h to obtain a slurry G;

[0066] S5. While maintaining the stirring speed at 1000 rpm, add 25 parts of boehmite to the slurry G obtained in S4, and continue stirring for 3 hours to obtain the final product.

[0067] Example 5

[0068] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0069] S1. Weigh 20 parts of sodium metasilicate, 8 parts of boron oxide, 10 parts of sodium hexametaphosphate, 8 parts of succinic acid, 20 parts of calcium carbonate, and 80 parts of water according to mass;

[0070] S2. Mix 20 parts of sodium metasilicate with 20 parts of water, stir at 150 rpm for 1 hour, and stir to prepare slurry A; mix 8 parts of boron oxide with 30 parts of water, stir at 400 rpm for 1 hour, and stir to prepare slurry B; stir slurry A and slurry B at 400 rpm for 2 hours to obtain slurry C;

[0071] S3: 10 parts of sodium hexametaphosphate and 20 parts of water were stirred at a speed of 360 rpm for 1 hour to be uniformly mixed to form slurry D, and then slurry D was added to slurry C obtained in S2 at a stirring speed of 450 rpm. After the addition, the temperature was raised to 100° C. and the stirring and heating speed was maintained for 2 hours to obtain slurry E;

[0072] S4. 8 parts of succinic acid and the remaining 10 parts of water were stirred at a speed of 150 rpm for 0.5 h, mixed and uniformly prepared into a solution F, and then added to the slurry E obtained in S3, maintained at a temperature of 100 ° C, and stirred at a speed of 900 rpm for 1 h to obtain a slurry G;

[0073] S5. While maintaining the stirring speed at 900 rpm, add 20 parts of calcium carbonate to the slurry G obtained in S4, and continue stirring for 2 hours to obtain the final product.

[0074] Example 6

[0075] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0076] S1. Weigh 25 parts of potassium metasilicate, 20 parts of calcium borate, 12 parts of hypophosphorous acid, 2 parts of propionic acid, 25 parts of dolomite, and 80 parts of water according to mass;

[0077] S2. Mix 25 parts of potassium metasilicate with 20 parts of water, stir at 300 rpm for 1 hour, and stir to prepare slurry A; mix 20 parts of calcium borate with 40 parts of water, stir at 400 rpm for 1 hour, and stir to prepare slurry B; mix slurry A and slurry B at 400 rpm to obtain slurry C;

[0078] S3: 12 parts of hypophosphorous acid and 12 parts of water are mixed and stirred at a speed of 120 rpm for 1 hour to obtain slurry D after being evenly mixed. Then, slurry D is added to slurry C obtained in S2 at a stirring speed of 900 rpm. After the addition, the temperature is raised to 100° C. and the stirring and heating speed is maintained for 3 hours to obtain slurry E.

[0079] S4. 2 parts of propionic acid and the remaining 8 parts of water were stirred at a speed of 150 rpm for 0.5 h, mixed and uniformly prepared as solution F, and then added to the slurry E obtained in S3, maintained at a temperature of 100 ° C, and stirred at a speed of 900 rpm for 2 h to obtain slurry G;

[0080] S5. While maintaining the stirring speed at 1200 rpm, add 25 parts of dolomite to the slurry G obtained in S4, and continue stirring for 2 hours to obtain the final product.

[0081] Example 7

[0082] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0083] S1. Weigh 30 parts of lithium water glass, 10 parts of boric acid, 12 parts of sodium hypophosphite, 8 parts of acetic acid, 40 parts of magnesium carbonate and 90 parts of water according to mass;

[0084] S2. 30 parts of lithium water glass were mixed with 30 parts of water, stirred at a speed of 150 rpm for 1 hour, and then uniformly stirred to prepare slurry A; 10 parts of boric acid were mixed with 30 parts of water, stirred at a speed of 300 rpm for 1 hour, and then uniformly stirred to prepare slurry B; slurry A and slurry B were mixed and stirred at a speed of 600 rpm to obtain slurry C;

[0085] S3: 12 parts of hypophosphorous acid and 18 parts of water were mixed, stirred at 120 rpm for 1 hour, and the mixture was uniformly prepared into slurry D. Then, slurry D was added into slurry C obtained in S2, and the stirring speed was 900 rpm. After the addition, the temperature was raised to 75° C., and the stirring and heating speed was maintained for 2 hours to obtain slurry E.

[0086] S4. 8 parts of acetic acid and the remaining 12 parts of water were stirred at a speed of 150 rpm for 0.5 h, mixed and uniformly prepared as solution F, and then added to the slurry E obtained in S3, maintained at a temperature of 75 ° C, and stirred at a speed of 900 rpm for 1 h to obtain slurry G;

[0087] S5. While maintaining the stirring speed at 1200 rpm, 40 parts of magnesium carbonate were added to the slurry G obtained in S4, and the mixture was stirred for 2 hours to obtain the final product.

[0088] Example 8

[0089] A method for preparing a flame retardant and heat insulating foamed ceramic precursor comprises the following steps:

[0090] S1. Weigh 20 parts of sodium water glass, 20 parts of potassium metaborate, 10 parts of sodium phosphite, 10 parts of formic acid, 25 parts of calcium oxalate, and 100 parts of water according to mass;

[0091] S2. 20 parts of sodium water glass were mixed with 20 parts of water, stirred at a speed of 150 rpm for 1 hour, and the mixture was uniformly stirred to form slurry A; 20 parts of potassium metaborate were mixed with 45 parts of water, stirred at a speed of 400 rpm for 1 hour, and the mixture was uniformly stirred to form slurry B; slurry A and slurry B were mixed and stirred at a speed of 400 rpm to obtain slurry C;

[0092] S3: 10 parts of sodium phosphite and 25 parts of water were mixed, stirred at a speed of 200 rpm for 1 hour, and the mixture was uniformly prepared into slurry D, and then slurry D was added to slurry C obtained in S2 at a stirring speed of 600 rpm. After the addition, the temperature was raised to 65° C. and the stirring and heating speed was maintained for 2 hours to obtain slurry E;

[0093] S4. 10 parts of formic acid and the remaining 10 parts of water were stirred at a speed of 150 rpm for 0.5 h, mixed and uniformly prepared as solution F, and then added to the slurry E obtained in S3, maintained at a temperature of 65 ° C, and stirred at a speed of 900 rpm for 2 h to obtain slurry G;

[0094] S5. While maintaining the stirring speed at 900 rpm, add 25 parts of calcium oxalate to the slurry G obtained in S4, and continue stirring for 2 hours to obtain the final product.

[0095] Comparative Example 1

[0096] A method for preparing a foamed ceramic precursor comprises the following steps:

[0097] S1. Weigh 20 parts of potassium water glass, 18 parts of sodium metaborate, 12 parts of sodium phosphate, 12 parts of acetic acid, 30 parts of aluminum hydroxide, and 90 parts of water according to mass;

[0098] S2. 20 parts of potassium water glass were mixed with 15 parts of water, stirred at a speed of 30 rpm for 1 hour, and prepared as slurry A; 18 parts of sodium metaborate were mixed with 35 parts of water, stirred at a speed of 250 rpm for 1 hour, and after stirring, they were uniformly prepared as slurry B; slurry A and slurry B were stirred and mixed at a speed of 100 rpm for 1 hour to obtain slurry C;

[0099] S3. 12 parts of sodium phosphate and 30 parts of water were stirred at a speed of 200 rpm for 1 hour to uniformly prepare slurry D, and then slurry D was added to slurry C obtained in S2 at a stirring speed of 400 rpm. After the addition, the temperature was raised to 90° C. and the stirring and heating speed was maintained for 2 hours to obtain slurry E;

[0100] S4. 12 parts of acetic acid and the remaining 10 parts of water were stirred at 30 rpm for 0.5 h to mix and uniformly prepare solution F, and then added to the slurry E obtained in S3, maintained at 90 ° C, and stirred at 400 rpm for 2 h to obtain slurry G;

[0101] Comparative Example 2

[0102] S1. Weigh 20 parts of sodium water glass, 20 parts of potassium metaborate, 10 parts of sodium phosphite, 25 parts of calcium oxalate, and 100 parts of water according to mass;

[0103] S2. 20 parts of sodium water glass were mixed with 20 parts of water, stirred at a speed of 150 rpm for 1 hour, and the mixture was uniformly stirred to form slurry A; 20 parts of potassium metaborate were mixed with 45 parts of water, stirred at a speed of 400 rpm for 1 hour, and the mixture was uniformly stirred to form slurry B; slurry A and slurry B were mixed and stirred at a speed of 400 rpm to obtain slurry C;

[0104] S3: 10 parts of sodium phosphite and 25 parts of water were mixed, stirred at a speed of 200 rpm for 1 hour, and the mixture was uniformly prepared into slurry D, and then slurry D was added to slurry C obtained in S2 at a stirring speed of 600 rpm. After the addition, the temperature was raised to 65° C. and the stirring and heating speed was maintained for 2 hours to obtain slurry E;

[0105] S4. While maintaining the stirring speed at 900 rpm, add 25 parts of calcium oxalate to the slurry G obtained in S3, and continue stirring for 2 hours to obtain the final product.

[0106] The components and weight proportions of Examples 1-8 and Comparative Examples 1-2 are shown in the following table.

[0107] Table 1 Raw material components and weight percentages of Examples 1-8 and Comparative Examples 1-2

[0108]

[0109]

[0110] Comparative Example 3

[0111] TE800-HS foam silicone pad with a thickness of 5 mm is commercially available for flame retardant insulation.

[0112] Comparative Example 4

[0113] UG450 aerogel composite material with a thickness of 3 mm is commercially available for flame retardant and thermal insulation.

[0114] The above samples were subjected to performance tests, and the specific test process is as follows:

[0115] (1) The flame retardant and heat insulating foamed ceramic precursor synthesized in Example 2 was coated on a ceramic fiber with a thickness of 3 mm. The coating thickness was about 1 mm. After being dried in an oven, it was placed in a muffle furnace. The photo before calcination is shown in the attached figure. Figure 2 After calcination at 400℃ for 20min, the flame retardant thermal insulation foamed ceramic precursor coating on the surface of the ceramic fiber foamed significantly, see attached Figure 3 At the same time, in order to test the flame retardant and heat insulation effect, a thermocouple was attached to the back of the dried sample with double-sided tape to measure the temperature. The front side coated with the flame retardant and heat insulation foam ceramic precursor was directly burned with a butane spray gun. After burning the front side for 2 minutes, the back side temperature was 120℃, and the sample thickness expanded to 18mm; after burning for 5 minutes, the back side temperature was 190℃, and the sample thickness expanded to 20mm.

[0116] (2) The flame-retardant and heat-insulating foamed ceramic precursor synthesized in Example 5 was coated on the surface of 304 stainless steel with a coating thickness of about 1 mm. After drying in an oven, it was directly burned with a butane torch. After continuous burning for 10 minutes, the coating thickness expanded to 28 mm, the stainless steel had no obvious change, and the back surface temperature reached 190°C.

[0117] (3) The flame retardant and heat insulating foamed ceramic precursor synthesized in Example 6 was coated between two layers of ceramic fibers (3 mm thick) with a coating thickness of about 0.5 mm. After being dried in an oven, it was placed in a muffle furnace and calcined at 700°C for 20 min. The sample was obviously foamed with a foam thickness of more than 10 mm, as shown in the attached Figure 4 .

[0118] (4) The foamed ceramic precursor synthesized in Example 8 is brushed on the surface of a metal or ceramic substrate material with a coating thickness of about 1 mm. It can be completely dried by baking at 100° C. for 3 to 5 minutes to form a thin film with strong adhesion.

[0119] (5) The foamed ceramic precursor synthesized in Comparative Example 1 was coated on a ceramic fiber with a thickness of 3 mm, and the coating thickness was about 1 mm. After being dried in an oven, it was placed in a muffle furnace. After being calcined at 400°C for 20 minutes, the flame retardant and heat insulating foamed ceramic precursor coating on the surface of the ceramic fiber was not obviously foamed, as shown in the attached Figure 5 At the same time, in order to test the flame retardant and heat insulation effect, a thermocouple was attached to the back of the dried sample with double-sided tape to measure the temperature. The front side coated with the flame retardant and heat insulation foam ceramic precursor was directly burned with a butane spray gun. After burning the front side for 2 minutes, the back side temperature was 220℃, and the sample thickness expanded to 6mm; after burning for 5 minutes, the back side temperature was 330℃, and the sample thickness expanded to 5mm.

[0120] (6) The flame retardant and heat insulating foamed ceramic precursor synthesized in Comparative Example 2 lacks an organic acid as a neutralizing agent, so the entire slurry remains strongly alkaline. A coating of the same thickness is not easy to dry even after being baked at 100°C for 20 minutes. After the temperature is increased to 130°C and dried, the coating is powdered to form loose particles that cannot adhere to the base material.

[0121] (7) The 5 mm thick foamed silicone pad of Comparative Example 3 was used to stick a thermocouple on the back with double-sided tape to measure the temperature. The front side was directly burned with a butane torch. After burning for 50 seconds, the foamed silicone pad had been burned through by the flame and the temperature reached 500°C. See attached for related photos. Figure 6 .

[0122] (8) The 3 mm thick aerogel composite material of Comparative Example 4 was used to stick a thermocouple on the back with double-sided tape to measure the temperature. The front side was burned directly with a butane torch. After burning for 60 seconds, the back side temperature reached 300°C. Related photos are attached. Figure 7 .

[0123] It can be seen from the above test results that the flame retardant and heat insulating foamed ceramic precursor prepared by the present invention with 20-30 parts of silicate, 10-20 parts of boron-containing compounds, 1-15 parts of organic acids, 1-20 parts of phosphorus-containing compounds, 10-40 parts of foaming agents, and 20-100 parts of water has excellent flame retardant and heat insulating properties. After high-temperature calcination, the foaming thickness of Example 2, Example 5 and Example 6 exceeds 10 mm, the back temperature is lower than 200 ° C, the foaming volume is large, and the heat insulation effect is good. Compared with each embodiment, the comparative example 1 lacks a foaming agent, the foaming effect is not good, and the heat transfer cannot be well blocked. The flame retardant and heat insulating foamed ceramic precursor synthesized in the comparative example 2, due to the lack of organic acid as a neutralizing agent, the entire slurry remains strongly alkaline and is not easy to dry. After the temperature is increased, the coating is powdered to form loose particles that cannot be attached to the base material. However, after the 5 mm thick foamed silicone pad of Comparative Example 3 and the 3 mm thick aerogel composite material of Comparative Example 4 were directly burned by a butane torch from the front, the temperature reached over 300° C., which could not meet the flame retardant and heat insulating performance requirements.

[0124] In summary, the flame retardant and heat insulating foamed ceramic precursor prepared by a specific component ratio in the present invention has excellent flame retardant and heat insulating effects. When subjected to heating, high temperature or open flame, decomposition reaction and cross-linking reaction occur to form an in-situ foamed ceramic flame retardant layer, which can play an active fire prevention role and has excellent flame retardant and heat insulating effects. It is suitable for a variety of chemical power sources, electrical equipment, and electronic equipment.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A flame retardant and heat insulating foamed ceramic precursor, characterized in that: The invention comprises the following components by weight: 20-30 parts of silicate, 10-20 parts of boron-containing compound, 1-15 parts of organic acid, 1-20 parts of phosphorus-containing compound, 10-40 parts of foaming agent and 20-100 parts of water.

2. The flame retardant and thermal insulating foamed ceramic precursor according to claim 1, characterized in that: The silicate is one or more of sodium water glass, potassium water glass, lithium water glass, sodium metasilicate and potassium metasilicate.

3. The flame retardant and thermal insulating foamed ceramic precursor according to claim 1, characterized in that: The boron-containing compound is one or more of sodium borate, potassium borate, magnesium borate, calcium borate, boric acid, and boron oxide.

4. The flame retardant and thermal insulating foamed ceramic precursor according to claim 1, characterized in that: The organic acid is one or more of formic acid, acetic acid, propionic acid, oxalic acid, malonic acid, and succinic acid.

5. The flame retardant and thermal insulating foamed ceramic precursor according to claim 1, characterized in that: The phosphorus-containing compound is one or more of phosphoric acid, hypophosphorous acid, phosphorous acid, sodium phosphate, sodium metaphosphate, sodium hypophosphite, and sodium phosphite.

6. The flame retardant and heat insulating foamed ceramic precursor according to claim 1, characterized in that: The foaming agent is one or more of magnesium hydroxide, basic magnesium carbonate, aluminum hydroxide, boehmite, calcium carbonate, magnesium carbonate, calcium oxalate, and dolomite.

7. A method for preparing a flame retardant and thermal insulating foamed ceramic precursor according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Weigh each component according to mass; S2. Mixing the silicate with an appropriate amount of water until the silicate is fully dissolved, stirring evenly and configuring it as slurry A; mixing the boron-containing compound with an appropriate amount of water until the boron-containing compound is fully dissolved, stirring evenly and configuring it as slurry B; mixing slurry A and slurry B, stirring evenly and obtaining slurry C; S3. Mixing the phosphorus-containing compound with an appropriate amount of water until the phosphorus-containing compound is fully dissolved to prepare slurry D, adding slurry D to slurry C obtained in S2 while stirring, and heating to obtain slurry E; S4. The organic acid and the remaining amount of water are mixed uniformly to form a solution F, which is added to the slurry E obtained in S3 while being heated and stirred to obtain a slurry G; S5. While maintaining stirring, add the foaming agent powder to the slurry G obtained in S4, and stir evenly to obtain the final product.

8. The method for preparing the flame retardant and thermal insulating foamed ceramic precursor according to claim 7, characterized in that: The heating temperature in S3 is 50-100°C.

9. The method for preparing the flame retardant and thermal insulating foamed ceramic precursor according to claim 7, characterized in that: The stirring speed in S2 and S3 is 30-600 rpm, and the stirring speed in S4 and S5 is 100-1200 rpm.

Citation Information

Patent Citations

  • A kind of magnesium oxysulfate cement lightweight foam brick and preparation method thereof

    CN106673588B